The relationship between the zero-violence program in improving cadet parenting patterns at BPSDM transportation service schools - Bagas Desta Ramadhan; Yeti Komalasari; Sukahir Sukahir; Jhellyananda Putri; Randa Agusta Pratama; M. Agrist P. Ramadhan; Minulya Eska Nugraha (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The high rate of violence in official schools occurs because of the gap between juniors and seniors, which is triggered by the seniority hierarchy. The Zero Violence Program is an effort by BPSDM Transportation to create a school environment that is free from physical, verbal and psychological violence. This research aims to analyze the relationship between the Zero Violence program and the parenting patterns of cadet parents at the BPSDM Transportation official school. Type of quantitative research with a correlational approach, sample size 354, instrument testing with validity and reliability, data analysis techniques using IBM SPSS series 26 software with correlation test. The results of the correlation test research show a significant relationship between the Zero Violence Program variable and the parenting patterns of cadet parents at the BPSDM Transportation official school. Furthermore, the zero violence program is expected to become part of the daily culture for cadets.